Controlled Synthesis of Thorium and Uranium Oxide Nanocrystals. Issue 17 (4th March 2013) - Hudry, Damien; Apostolidis, Christos; Walter, Olaf; Gouder, Thomas; Courtois, Eglantine; Kübel, Christian; Meyer, Daniel
Abstract Very little is known about the size and shape effects on the properties of actinide compounds. As a consequence, the controlled synthesis of well‐defined actinide‐based nanocrystals constitutes a fundamental step before studying their corresponding properties. In this paper, we report on the non‐aqueous surfactant‐assisted synthesis of thorium and uranium oxide nanocrystals. The final characteristics of thorium and uranium oxide nanocrystals can be easily tuned by controlling a few experimental parameters such as the nature of the actinide precursor and the composition of the organic system (e.g., the chemical nature of the surfactants and their relative concentrations). Additionally, the influence of these parameters on the outcome of the synthesis is highly dependent on the nature of the actinide element (thorium versus uranium). By using optimised experimental conditions, monodisperse isotropic uranium oxide nanocrystals with different sizes (4.5 and 10.7 nm) as well as branched nanocrystals (overall size ca. 5 nm), nanodots (ca. 4 nm) and nanorods (with ultra‐small diameters of 1 nm) of thorium oxide were synthesised.